Development of a Mathematical Model for Heavy Oil Recovery using Heat Assisted WAG with Chemical Additives - Musa, Sami A (2010)
During WAG operation, early breakthrough and gravity segregation of the gas occur which limits the efficiency of the process. To combat this, we propose to use Heat Assisted WAG with Chemical Additives. To simulate the oil recovery by the proposed technique requires formulating an accurate mathematical model incorporating the important physical phenomena occurring during the process. In this study we present a mathematical model for the numerical simulation of the process to study the effect of the different parameters which can affect the recovery efficiency of the production of viscous oil. This paper discusses a 1-D compositional mathematical model of the process. The fully implicit finite difference approximation is used to convert the partial differential equation of the model into algebraic equations. The non linear Newtown-Raphson method is used for the solution of the resulting equations. The Jacobian of the residual equations is evaluated. We expect that application of the new developed recovery technique will improve oil recovery for many reservoirs containing viscous oil with a limited mobility and for recovery of residual oil at reservoir condition.